2019
DOI: 10.1111/fme.12334
|View full text |Cite
|
Sign up to set email alerts
|

Using fish landing sites and markets information towards quantification of the blue economy to enhance fisheries management

Abstract: Fisheries management uses important fish market information and information from Communication Technology (ICT) to improve fish trade by identifying inefficiencies, inequity and post‐harvest losses. The current study reports fisheries output using ICT at major landing sites and markets in Kenya and Uganda from the Kenya Marine and Fisheries Research Institute (KMFRI) Enhanced Fish Market Information Service (EFMIS) database for 2009 – 2017. Catch assessment survey data validated the use of market data in drawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…A fluctuating trend was exhibited for Lake Victoria tilapia in the major landing sites and markets. This could be related to disruption of market because of movement restrictions from some towns such as Nairobi, which has been the major market ( Aura et al, 2019 ). A similar scenario was noted when China imposed lockdowns and travel restrictions ( Tester, 2020 , Dao, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A fluctuating trend was exhibited for Lake Victoria tilapia in the major landing sites and markets. This could be related to disruption of market because of movement restrictions from some towns such as Nairobi, which has been the major market ( Aura et al, 2019 ). A similar scenario was noted when China imposed lockdowns and travel restrictions ( Tester, 2020 , Dao, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The changes in fish landing and prices before and after flooding and Covid-19 were obtained by comparing data collected between 2009 and 2017 before (before 14th March 2020) and during (after 14th March 2020) using the Electronic Fish Market Information System (EFMIS). EFMIS is an ICT (Information and Communication Technology Authority) pilot project, being implemented around Lake Victoria in Kenya based on mobile phones to provide information on landings in terms of species and prices at fish landing sites and markets ( Aura et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, [51] agreed that the employment of IT who is able to reduce price volatility in agricultural markets in enhancing the efficiency of agricultural markets. Researcher [52] reported that sharing information in IT platforms causing an efficient and equitable fish trade. Reducing the process number of middlemen have an impact on reducing wastage and volatility of fish prices.…”
Section: Previous Studiesmentioning
confidence: 99%